ICAP Taxonomy of Modes of Cognitive Engagement: A Learner-Centered Theory Focusing on Observable Engagement Behaviors - Cheng, Xiaoqiao (Science Insights Education Frontiers, 2023)
Historically, there have been a number of impactful education theories that used the taxonomy as a classification device, such as the Bloom taxonomy of educational objectives and Gagne taxonomy of learning outcomes. The Bloom taxonomy of educational objectives was developed in the 1950s by the U.S. Committee of College and University Examiners under the leadership of Dr. Benjamin Bloom, which categorizes educational objectives into three domains: cognitive, affective, and psychomotor. Among them, the cognitive domain (the main concern of their research) contains six major classes: knowledge, comprehension, application, analysis, synthesis, evaluation. They are arranged in a hierarchical order with the objectives in one class built on the behaviors found in the preceding classes. Its primary purpose is to provide classification of goals of the educational system for all teachers, administrators, professional specialists, and research workers who deal with curricular and evaluation problems (Committee of College and University Examiners, 1956). Gagne’s theory approaches learning from the viewpoint of the instruction. Under his taxonomy, the five categories of learning outcomes are verbal information, intellectual skills, cognitive strategies, motor skills, and attitudes, each of which requires necessary conditions to achieve and corresponds to specific principles of instructional events (Gagne, 1984).